Developing Critical Thinking in Grades 3-4: Inclusive, Student-Centric Writing Approaches - Nalls, Irdawati (International Journal of Asian Education, 2024)
This study aims to analyze the impact of high-stakes testing practices in Asian countries, particularly Singapore, on students' learning outcomes and overall intellectual development. While the education system that focuses on standardized testing has garnered international recognition, it also raises concerns about the dominance of rote memorization over the development of critical thinking skills. This research proposes integrating Bronfenbrenner's Ecological Systems Theory and Critical Theory in Education as a framework for curriculum design to create a more balanced educational approach. The research method employed was observational and participatory, conducted over one academic year in a 3rd and 4th-grade classroom in Singapore. Data were collected through classroom observations, student writing samples, and parental involvement in the writing program. Parental involvement included weekly writing facilitation sessions and providing insights into the influence of parents on student development. The results of the study indicate that high-stakes testing practices contribute to improved academic performance but tend to limit students' critical thinking abilities. The use of a holistic approach in the curriculum, emphasizing student engagement and environmental support, proved effective in fostering analytical thinking. The implications of this study highlight the need to balance test preparation with the development of critical thinking skills in the education system, ensuring that students not only excel academically but are also equipped to think critically and adapt to global contexts.